Realizing The Profile of Pancasila Students through Bebentengan Traditional Games in Elementary School Students - Hidayatullah, Hidayatullah; Hidayat , Sholeh; Jamaludin, Ujang; Leksono, Suroso Mukti; Prawiyogi, Anggy Giri (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2023)
Realizing the profile of Pancasila students is a lofty goal that is the target of the Government of Indonesia. The implementation is through a learning process in academic units to realize these expectations. This study uses a descriptive qualitative approach using the literature study method and examines the values contained in the traditional Bebentengan game associated with the profile of Pancasila students. This research aims to discover the steps to realize the Pancasila student profile for elementary school students, which is integrated into the learning process through the game Bebentengan. The study results show that Bebentengan games can grow and realize the profile of Pancasila students. This can be seen from the character of the Bebentengan game, namely, working together, helping each other, and working hard.